CRITICAL THINKING SKILLS AND STUDENTS' LEARNING OUTCOMES IN LEARNING BIOLOGY OF MUSHROOM CONCEPT AT SMA NEGERI 4 BARABAI - Norhasanah Norhasanah; Ruswaty Ruswaty; Fahmi Fahmi; Marnina Ika Putri (Journal of Banua Science Education, 2021)
Teachers as learning agents must be able to present the learning process contextually by involving the active participation of students. Some students learn best when they have the opportunity to interact with real objects through inquiry activities that will help students deepen their understanding of a concept. Inquiry learning is one that can be adapted to students' abilities, can build cognitive structures, and can motivate students to think critically. This research is classified as descriptive research. The subjects of the research were students of class X SMA Negeri 4 Barabai as many as 78 students in the 2015/2016 academic year on the mushroom group material. The research data were in the form of observations on students' critical thinking skills which were analyzed descriptively using categorical methods, namely very good (≥ 3), good (2-2.99), not good (1-1.99). While cognitive learning outcomes were obtained through tests and success was determined based on KKM = 67 with classical completeness 85%. The results showed that students' critical thinking skills were at least good, namely formulating hypotheses, designing experiments, conducting experiments, and making conclusions, while formulating problems, and analyzing data still needed improvement. Meanwhile, students' cognitive learning outcomes have not yet achieved minimal completeness. Keywords: critical thinking skills, learning outcomes, inquiry AbstrakGuru sebagai agen pembelajar harus mampu menyajikan proses pembelajaran secara kontekstual dengan melibatkan langsung peran serta siswa secara aktif. Sebagian siswa belajar dengan baik apabila mereka mendapat kesempatan berinteraksi dengan benda-benda nyata melalui aktivitas penyelidikan yang akan membantu siswa memperdalam pemahaman suatu konsep. Pembelajaran inkuiri merupakan salah satu pembelajaran yang dapat diadaptasikan dengan kemampuan siswa, dapat membangun struktur kognitif, dan dapat memotivasi siswa untuk berpikir kritis. Penelitian ini tergolong penelitian deskriptif. Subjek penelitian adalah siswa kelas X SMA Negeri 4 Barabai sebanyak 78 siswa tahun pelajaran 2015/2016 pada materi pokmok jamur. Data hasil penelitian berupa hasil observasi terhadap keterampilan berpikir kritis siswa yang dianalisis secara deskriptif dengan menggunakan kategorikal yakni sangat baik (≥ 3), baik (2-2,99), kurang baik (1-1,99). Sedangkan hasil belajar kognitif diperoleh melalui tes dan keberhasilan ditetapkan berdasarkan KKM = 67 dengan ketuntasan klasikal ≥ 85%. Hasil penelitian diperoleh bahwa keterampilan berpikir kritis siswa sekurang-kurangnya sudah baik, yakni merumuskan hipotesis, merancang percobaan, melakukan percobaan, dan membuat kesimpulan, sedangkan merumuskan masalah, dan menganalisis data masih perlu perbaikan. Sedangkan hasil belajar kognitif siswa belum mencapai ketuntasan minimal. Kata kunci: keterampilan berpikir kritis, hasil belajar, inkuiri